Quantitative Intracerebral Microdialysis Studies to Determine Unbound Extracellular Fluid Drug Concentrations in Discrete Areas of the Brain. Issue 1 (2nd April 2018) - Durk, Matthew R.
Abstract: Intracerebral microdialysis is a powerful technique for quantifying unbound brain extracellular fluid concentrations of drugs and drug candidates over time in live, conscious, freely moving animals. The results provide crucial information on the brain penetrance of the administered agent. This unit details the surgical procedures, study planning and execution, and data analysis required for a brain microdialysis study following intravenous infusion of a test substance to steady state. The accumulated data makes possible the determination of the area under the concentration–time curve ratio and steady‐state concentration ratio for unbound compound in rat brain extracellular fluid as compared to that in plasma (Kpu, u ). In vitro determination of the compound recovery from the probe, a critical parameter in a microdialysis study, is considered as well. © 2018 by John Wiley & Sons, Inc.